2009
DOI: 10.1007/s10584-009-9761-5
|View full text |Cite
|
Sign up to set email alerts
|

Sea level rise and tigers: predicted impacts to Bangladesh’s Sundarbans mangroves

Abstract: The Sundarbans mangrove ecosystem, shared by India and Bangladesh, is recognized as a global priority for biodiversity conservation. Sea level rise, due to climate change, threatens the long term persistence of the Sundarbans forests and its biodiversity. Among the forests' biota is the only tiger (Panthera tigris) population in the world adapted for life in mangrove forests. Prior predictions on the impacts of sea level rise on the Sundarbans have been hampered by coarse elevation data in this low-lying regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 18 publications
1
68
2
Order By: Relevance
“…The simulated mangrove losses due to RSLR by the end of 21 st century at the Bangladesh Sundarbans are much smaller than earlier estimates (e.g., Huq et al 1995;Loucks et al 2010), which are widely reported in discussions about Bangladesh and SLR. For example, Colette (2007) suggested that a 45 cm rise in global sea level by 2100 might lead to the destruction of 75 % of the Sundarbans mangroves suggesting significant differences on the DEM used in different studies; the DEM used by Loucks et al (2010) suggest that most of the Sundarbans will be below MSL for a SLR of +28 cm.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The simulated mangrove losses due to RSLR by the end of 21 st century at the Bangladesh Sundarbans are much smaller than earlier estimates (e.g., Huq et al 1995;Loucks et al 2010), which are widely reported in discussions about Bangladesh and SLR. For example, Colette (2007) suggested that a 45 cm rise in global sea level by 2100 might lead to the destruction of 75 % of the Sundarbans mangroves suggesting significant differences on the DEM used in different studies; the DEM used by Loucks et al (2010) suggest that most of the Sundarbans will be below MSL for a SLR of +28 cm.…”
Section: Discussioncontrasting
confidence: 53%
“…For example, Colette (2007) suggested that a 45 cm rise in global sea level by 2100 might lead to the destruction of 75 % of the Sundarbans mangroves suggesting significant differences on the DEM used in different studies; the DEM used by Loucks et al (2010) suggest that most of the Sundarbans will be below MSL for a SLR of +28 cm. However, in our study this level of inundation is only observed for the most extreme scenario (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geographical location of Bangladesh in South Asia, at the confluence of three large river systems -the Brahmaputra, the Ganges, and the Meghna -and north of the Bay of Bengal, renders it one of the most vulnerable places to floods and cyclones. Human-induced climate change exacerbates the problem, with its already manifested effects and the predicted rise in sea level of 0.3 m to 0.5 m by 2050 [1,2,3]. Climate models have revealed that the effects of climate change are not only affecting individual countries, but resulting in increased climate variations at regional levels [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have addressed this research gap by modelling the habitat suitability of four large threatened mammals under different climate scenarios across their entire distribution range. (Table 1 and Table A1for details), and their main threats are the combined effects of habitat loss, forest fragmentation, human interference, hunting and global climate change (Alamgir et al 2015;IUCN 2016;Loucks et al 2010;Srinivasulu & Srinivasulu 2012). These species are already extinct locally in several countries, and the remaining disjunct populations are declining (IUCN 2016;Sala et al 2000;Thomas et al 2004).…”
Section: Introductionmentioning
confidence: 99%